POLITICAL WILL PEMILIH FIGUR KEPEMIMPINAN CALON KEPALA DESA - Rohmat Rohmat (Millah: Journal of Religious Studies, 2013)
The study aims to analyze political will of the voters the leadership figure of the village chief candidate in rural community development in the Sanggung village, Gatak District, Sukoharjo, 2012. This study used a descriptive approach. The population in this study is 1 5 0 0 suffrage and sample is 1 00 suffrage. The instruments to collect data using questionnaires. The data analysis using the percentage percentile). The results of this study found that political will of the voters the leadership figure of the village chief candidate in doing the task of rural community development, that is: the initiatives (98% ); the priority (8 2% ); oriented mobilization of community development (5 0% ); emphasizing the rule of law in the form of severe punishment for corruption (4 0% ); business sustainability minded (99% ); attention try giving passion and spirit new life and eliminate the monotony of village life (97% ); influential in improving the socio-economic welfare (1 0 0% ); improving education (8 4% ); undertake modernization in the field of transport and technology (1 0 0% ); did not contest the figure gender prospective village chief (6 9% ) and the changes (94%).